Analysis on Quality of Service at Design and Engineering Department by Using Servqual, IPA, and QFD Methods - Heru Indrawidjajanto; Bambang Syairudin (Institut Teknologi Sepuluh Nopember, 2020)
PT. Semen Indonesia develops the cement business in Indonesia by striving to be at the forefront in the world of the cement manufacturing business, as well as trying to be a calculated player in the cement derivative business. To achieve this goal, the Department of Design & Engineering, as a supporting function, always strives to provide the best service for customers, namely other work units within PT. Semen Indonesia group. There are 20 service attributes used as indicators in the questionnaire, covering five dimensions of service quality, namely tangible, empathy, responsiveness, reliability, and assurance. The measurement of the level of customer satisfaction of the Design & Engineering Department is carried out by Service Quality (Servqual), Importance Performance Analysis (IPA), Quality Function Deployment (QFD) methods. The results show that based on Servqual analysis, in general, customers are still not satisfied with the resulting performance. Based on the results of the IPA analysis, five service attributes are the top priority for improvement, namely: coordination with customers, completion of Engineering work according to the agreed time, solutions to customer problems, able to meet customer needs, and product engineering by customer desires. Based on the results of the QFD analysis, there are six strategic steps in the work program carried out to improve service quality in the Design & Engineering Department.